2014
DOI: 10.5194/cp-10-569-2014
|View full text |Cite
|
Sign up to set email alerts
|

Towards an improved organic carbon budget for the western Barents Sea shelf

Abstract: Abstract. There is generally a lack of knowledge on how marine organic carbon accumulation is linked to vertical export and primary productivity patterns in the Arctic Ocean. Despite the fact that annual primary production in the Arctic has increased as a consequence of shrinking sea ice, its effect on flux, preservation, and accumulation of organic carbon is still not well understood. In this study, a multi-proxy geochemical and organic-sedimentological approach is coupled with organic facies modelling, focus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 79 publications
(115 reference statements)
7
24
0
Order By: Relevance
“…1) used here on the core data accounts for carbon flux through the water column and processes affecting burial in the sediments (see [28,35,40] for details on the equations).…”
Section: Primary Productivity Reconstructionmentioning
confidence: 99%
See 4 more Smart Citations
“…1) used here on the core data accounts for carbon flux through the water column and processes affecting burial in the sediments (see [28,35,40] for details on the equations).…”
Section: Primary Productivity Reconstructionmentioning
confidence: 99%
“…Knies and Martinez [29] showed that the marine nitrogen endmember is represented by its organic fraction, i.e. %N org (of total) = 100 %, and a linear regression analysis of %N org and d 13 C org gives a marine d 13 C org endmember of -20.1 % at 100 % N org [29,40]. We interpret these endmembers (from the surface sample data set) as representative for the Barents Sea and use them to calculate the terrestrial (TOM) and marine (MOC) organic carbon fractions and to calibrate the organic facies model.…”
Section: Organic Matter Sourcesmentioning
confidence: 99%
See 3 more Smart Citations